Current State of Problem of Mathematical Modeling and Prognosis of the Epidemic Process - A. A. Lopatin; V. A. Safronov; A. S. Razdorskiy; E. V. Kouklev (Проблемы особо опасных инфекций, 2010)
Short systematic review on the modeling methods in medicine and epidemiology is presented. In particular, special native and foreign examples of application of mathematical modeling and prognosis of epidemic process are described.